2004
DOI: 10.1137/s1052623403426398
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Boundedness of a Preconditioned Normal Matrix Used in Interior-Point Methods

Abstract: Abstract. Solving systems of linear equations with "normal" matrices of the form AD 2 A T is a key ingredient in the computation of search directions for interior-point algorithms. In this article, we establish that a well-known basis preconditioner for such systems of linear equations produces scaled matrices with uniformly bounded condition numbers as D varies over the set of all positive diagonal matrices. In particular, we show that when A is the node-arc incidence matrix of a connected directed graph with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 12 publications
0
19
0
10
Order By: Relevance
“…Since the condition number of the normal matrix AD 2 A T may become excessively large on degenerate LP problems (see e.g., [13]), the maximum weight basis (MWB) preconditioner T introduced in [19,22,25] is used to better condition this matrix, and an approximate solution of the resulting equivalent system with coefficient matrix T AD 2 A T T T is then computed. By using a result obtained in [17], which establishes that the condition number of T AD 2 A T T T is uniformly bounded by a quantity depending only on A, Monteiro and O'Neal [16] showed that the number of inner iterations of the algorithm in [16] can be uniformly bounded by a constant depending on n and A.…”
mentioning
confidence: 99%
“…Since the condition number of the normal matrix AD 2 A T may become excessively large on degenerate LP problems (see e.g., [13]), the maximum weight basis (MWB) preconditioner T introduced in [19,22,25] is used to better condition this matrix, and an approximate solution of the resulting equivalent system with coefficient matrix T AD 2 A T T T is then computed. By using a result obtained in [17], which establishes that the condition number of T AD 2 A T T T is uniformly bounded by a quantity depending only on A, Monteiro and O'Neal [16] showed that the number of inner iterations of the algorithm in [16] can be uniformly bounded by a constant depending on n and A.…”
mentioning
confidence: 99%
“…One feature of the MWB preconditionerT discussed in Subsection 3.2 is that it satisfieŝ T HT T I , as was shown in [20]. Thus, the Adaptive PCG (APCG) method in [19] may be used as the iterative solver to determine an approximate solution to the preconditioned HANE.…”
Section: Discussionmentioning
confidence: 99%
“…Baseados em [11] e [7], este trabalho propõe reordenar as colunas da matriz A em ordem decrescente h j = d 1/2 jj a j e dividir as colunas ordenadas em grupos de acordo com um critério de reordenamento.…”
Section: Novo Critério De Ordenamentounclassified